Curricula for Meaningful Work through Listening in a Different Voice - Almond, Devon (Allies for Education, 2020)
Curricula for meaningful work is becoming increasingly important in today’s societies and cultures. Despite the fact that most students desire meaningful work, there are few indications that curricular practices to facilitate meaningful work are being widely implemented at K-12 schools, colleges, and universities. This article illuminates the importance of implementing curricular practices that facilitate students to listen in a different voice—that is, to listen for vocational callings.